Interpretación detallada y visualización en tres dimensiones, del flujo de escombros de noviembre 13 de 1985 en armero (tolima, colombia), utilizando imágenes de satélite landsat tm 5 (2001)
On November 13th of 1985, the city of Armero was destroyed by a debris flow generated by a reactivation of the Nevado del Ruiz Volcano, located in the middle third of the Central Cordillera of Colombia.  Further studies have indicated that the flow ocurred in at least three main pulses, each one with different hydrodynamic characteristics, as was observed by the survivors of the tragedy. Landsat TM 5 data processing was carried out in subscenes taken before and after the debris flow sedimentation. False color composites were generated and combined with a digital terrain model and the geological information available, in order to create perspective views for visualizing the catastrophe magnitude and the flow characteristics. Taking advantage of Landsat TM 5 images high spectral resolution, a detailed interpretation of its three principal pulses was carried out, in order to improve the previous photointerpretations elaborated with panchromatic aerial photographs Despite its low spatial and temporal resolution, Landsat TM is a remote sensing powerful tool, which offers plenty of applications for hazard assesment of catastrophic lahars. By the time when the eruption of Nevado del Ruiz triggered the Armero debris flow, the access to Landsat TM 5 data would have played a very important role in that disaster's mitigation.